Covid-19 mortality needs age adjusting for international comparisons - Garcia-Calavaro, C; Paternina-Caicedo, A; Smith, AD; Harrison, LH; De la Hoz-Restrepo, F; Acosta, E; Riffe, T (Wiley, 2021)
Covid-19 had caused more than 1,4 million deaths worldwide by November 26th, 2020. Age is a strong predictor of Covid-19 mortality. Crude death rates have been used to compare the response of countries, however, this measure does not account for age structure. We report age-adjusted mortality and rates at similar timeframes, ~100 days from the 50th confirmed case, for 51 countries, as well as 50 states in the US and the District of Columbia. We found age-adjusted mortality rate at ~ 100 days is 18 times greater in New Jersey (largest mortality in the U.S.), compared to Maine (lowest mortality in the U.S). Similar patterns were present in world countries. In Japan, the age-adjusted mortality rate was 0.1; while in Peru was 47.6 at ~ 100 days of Covid-19 transmission (476 times higher). Europe, Latin America, and the US, resulted in highest age-adjusted mortality rates worldwide during the first 100 days of transmission. The data suggest that measures taken by different territories might be a factor for the different mortality rates across regions and countries worldwide. Age-adjustments are needed to compare mortality between populations with different age-structures. This article is protected by copyright. All rights reserved.